Influence of die geometry on performance in gradation extrusion using numerical simulation and analytical calculation. Issue 1 (2016) - Landgrebe, Dirk; Sterzing, Andreas; Schubert, Nadine; Bergmann, Markus
Abstract: Forming by gradation extrusion enables severe plastic deformation with a large gradient of plastic strain resulting in a correlating gradient of the microstructure. Materials with tailored properties can thus be provided. Controlling the gradation of the microstructure also requires knowledge of the interaction of forming process and a special die geometry. Based on an analytical calculation approach, different geometry variants are characterized. Additionally, selected geometrical variants are studied more comprehensively by numerical simulation. The mechanisms of the interaction and possibilities of influencing the deformation process by die design and process parameter optimization are presented and analyzed.